Analisis Electronic Word of Mouth Terhadap Purchase Intention Melalui Brand Image Sebagai Variabel Mediasi: Survey pada Konsumen Produk Baju Brand Nevada di Kota Sukabumi - Riana Aulia R; Kokom Komariah; Faizal Mulia Z (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine how much influence electronic word of mouth has on purchase intention through brand image as a mediating variable. The method used in this study is an associative method with a quantitative approach. The population in this study were Sukabumi City Residents, using the Cluster sampling method. This study was conducted by distributing online questionnaires to 125 respondents. The data analysis technique used in this study is Structural Equational Modeling (SEM) with the help of data processing using SmartPLS 3.2.9 software. The results of this study indicate that electronic word of mouth has a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on purchase intention, and brand image mediates positively and significantly the relationship is not effective between electronic word of mouth and purchase intention.